Effects of exercise based on ACSM recommendations on bone mineral density in individuals with osteoporosis: a systematic review and meta-analyses of randomized controlled trials - Cui, Wenlai; Li, Dong; Jiang, Yueshuai; Gao, Yang (Frontiers in Physiology, 2023)
To analyze the effects of different exercise dose on lumbar spine and femoral neck bone mineral density (BMD) in individuals with osteoporosis (OP).Design: A systematic search was conducted in four electronic databases, namely PubMed, Embase, Web of Science, and Cochrane, with the topic of the impact of exercise on BMD in individuals with OP. Randomized controlled trials comparing exercise intervention with no intervention were identified, and changes in lumbar spine and femoral neck BMD were reported and evaluated using standardized mean difference (SMD) and 95% confidence interval (95% CI). The intervention measures in the studies were evaluated and categorized as high adherence with the exercise testing and prescription recommendations for individuals with OP developed by the American College of Sports Medicine (ACSM) or low/uncertainty adherence with ACSM recommendations. A random effects model was used to conduct meta-analyses and compare the results between subgroups.Results: A total of 32 studies involving 2005 participants were included in the analyses, with 14 studies categorized as high adherence with ACSM recommendations and 18 studies categorized as low or uncertain adherence. In the analyses of lumbar spine BMD, 27 studies with 1539 participants were included. The combined SMD for the high adherence group was 0.31, while the combined SMD for the low or uncertain adherence group was 0.04. In the analyses of femoral neck BMD, 23 studies with 1606 participants were included. The combined SMD for the high adherence group was 0.45, while the combined SMD for the low or uncertain adherence group was 0.28. Within resistance exercise, the subgroup with high ACSM adherence had a greater impact on lumbar spine BMD compared to the subgroup with low or uncertain ACSM adherence (SMD: 0.08 > -0.04). Similarly, for femoral neck BMD, resistance exercise with high ACSM adherence had a higher SMD compared to exercise with low or uncertain ACSM adherence (SMD: 0.49 > 0.13).The results suggest that exercise interventions with high adherence to ACSM recommendations are more effective in improving lumbar spine and femoral neck BMD in individuals with OP compared to interventions with low or uncertain adherence to ACSM recommendations.